The Effect of Murotal Therapy and Environmental Therapy on the Behavior of Hallucination Patients in Rehabilitation - Bayu Seto Rindi Atmojo; Eko Riyanti (GLOBAL HEALTH SCIENCE GROUP, 2024)
Mental disorders are still a serious problem in the world today, the number of people suffering from mental disorders increases every year in various parts of the world. Murottal therapy is a therapy used in hallucinatory patients to overcome mental disorders such as listening to the voice of the Qur'an. Religious therapy (religious intervention) is useful in cases of mental disorders. Environmental therapy is an act of healing patients with mental disorders through manipulation and modification of elements in the environment and affects the healing process. Objective: To determine the effect of Murottal Therapy and Environmental Therapy on the Behavior of Hallucinatory Patients at the Tirto Jiwo Rehabilitation Center. Methods: In this study, researchers conducted quantitative research using the pre-experimental design method, one group pretest-posttest type. The population in this study were 40 patients who had hallucinatory behavior. The sampling technique used in this study was total sampling. Data was collected using a behavioral questionnaire. The test used was the Wilcoxon test. Results: The average score of pre-intervention behavior was 38,20 with a standard deviation of 9,332, while the average score of post-intervention was 67,95 with a standard deviation of 12,012. The results of the analysis showed that there was an influence of Murotal Therapy and Environmental Therapy on the behavior of hallucinatory patients at the Tirto Jiwo Rehabilitation Center with a p value of 0,000. Conclusion: There was an influence of Murotal Therapy and Environmental Therapy on the behavior of hallucinatory patients at the Tirto Jiwo Rehabilitation Center.